Altered early immune response after fracture and traumatic brain injury - Haffner-Luntzer, Melanie; Weber, Birte; Morioka, Kazuhito; Lackner, Ina; Fischer, Verena; Bahney, Chelsea; Ignatius, Anita; Kalbitz, Miriam; Marcucio, Ralph; Miclau, Theodore (Frontiers in Immunology, 2023)
Clinical and preclinical data suggest accelerated bone fracture healing in subjects with an additional traumatic brain injury (TBI). Mechanistically, altered metabolism and neuro-endocrine regulations have been shown to influence bone formation after combined fracture and TBI, thereby increasing the bone content in the fracture callus. However, the early inflammatory response towards fracture and TBI has not been investigated in detail so far. This is of great importance, since the early inflammatory phase of fracture healing is known to be essential for the initiation of downstream regenerative processes for adequate fracture repair. Therefore, we analyzed systemic and local inflammatory mediators and immune cells in mice which were exposed to fracture only or fracture + TBI 6h and 24h after injury. We found a dysregulated systemic immune response and significantly fewer neutrophils and mast cells locally in the fracture hematoma. Further, local CXCL10 expression was significantly decreased in the animals with combined trauma, which correlated significantly with the reduced mast cell numbers. Since mast cells and mast cell-derived CXCL10 have been shown to increase osteoclastogenesis, the reduced mast cell numbers might contribute to higher bone content in the fracture callus of fracture + TBI mice due to decreased callus remodeling.